Preparation and characterization of Meta-bromo-thiolactone calcium alginate nanoparticles - Esra Kamal Eltayb; Fadilah Sfouq Aleanizy; Fulwah Y. Alqahtani; Hamad M. Alkahtani; Siddique Akber Ansari; Ibrahim Alsarra (Saudi Pharmaceutical Journal, 2022)
Recently, the focus has been shifting toward Quorum sensing inhibitors which reduce Pseudomonas aeruginosa virulence factors, alleviating infections. In this work, me-ta-bromo-thiolactone (mBTL), a potent quorum and virulence inhibitor for the Pseudomonas aeruginosa strains, were formulated in calcium alginate nanoparticles (CANPs). Alginate is used as nutrients and as backbone virulence aspect for Pseudomonas and therefore was chosen. mBTL-loaded-CANPs were characterized for particle size, polydispersity index, zeta potential, morphology visualized by Transmission Electron Microscopy (TEM) and drug release profile. Chemical and physical analysis of formulated mBTL-loaded-CANPs were evaluated using Fourier transform infrared Spectroscopy (FTIR) and differential scanning calorimetry (DSC) and Physical stability of mBTL-loaded-CANPs assessed at various temperature 25 ± 1 °C, 4 ± 0.5 °C and −30° ± 1 °C over a period of 4 and 9 months. Synthesized CANPs showed nano-size particles ranging from 140 to 200 nm with spherical particles for plain CANPS and irregular shape for mBTL-loaded-CANPs with a sustainable release profile over 48hrs. FTIR showed stable structure of loaded-mBTL and DSC displayed no interaction between mBTL and polymer. State of released mBTL from CANPs kept at 25 °C, 4 °C and −30 °C over 4 and 9 months showed stable formula at room temperature which kept as a goal of nanoparticles storage. The findings of this study revealed successful preparation of mBTL-loaded-CANPs.